NOX1 promotes myocardial fibrosis and cardiac dysfunction via activating the TLR2/NF-κB pathway in diabetic cardiomyopathy - Zhang, Dandan; Li, Yilan; Wang, Weijie; Lang, Xueyan; Zhang, Yanxiu; Zhao, Qianqian; Yan, Jingru; Zhang, Yao (Frontiers in Pharmacology, 2022)
Diabetic cardiomyopathy (DCM) is a prevalent complication in patients with diabetes, resulting in high morbidity and mortality. However, the molecular mechanisms of which have yet to be fully elucidated. In this study, we investigated a novel target, NOX1, an isoform of superoxide-producing NADPH oxidase with key functional involvement in the pathophysiology of DCM. The DCM rat model was established by a high-fat diet combined with streptozotocin injections. DCM rats elicited myocardial fibrosis exacerbation, which was accompanied by a marked elevation of NOX1 expression in cardiac tissue. In particular, a specific NOX1 inhibitor, ML171, effectively decreased myocardial fibrosis and protected against cardiac dysfunction in DCM rats. Rat neonatal cardiac fibroblasts were incubated with high glucose (HG, 33 mM) as an in vitro model of DCM. We also observed that the expression of NOX1 was upregulated in HG-cultured cardiac fibroblasts. Silencing of NOX1 was found to attenuate myocardial fibrosis and oxidative stress in HG-induced cardiac fibroblasts. Further, the upregulation of NOX1 by hyperglycemia induced activation of the TLR2/NF-κB pathway both in vitro and in vivo, whereas these effects were significantly attenuated with NOX1 gene silence and further enhanced with NOX1 gene overexpression. In summary, we demonstrated that NOX1-induced activation of the TLR2/NF-κB pathway and increased reactive oxygen species production accumulation, ultimately increased myocardial fibrosis and deteriorated cardiac function in diabetic cardiomyopathy. Our study revealed that NOX1 was a potential therapeutic target for DCM.